GPS phase scintillation at high latitudes during geomagnetic storms of 7-17 March 2012, part 2: interhemispheric comparison - Prikryl, P.; Ghoddousi-Fard, R.; Spogli, L.; Mitchell, C.N.; Li, G.; Ning, B.; Cilliers, P.J.; Sreeja, V.; Aquino, M.; Terkildsen, M.; Jayachandran, P.T.; Jiao, Y.; et al. (European Geosciences Union, 2015)
During the ascending phase of solar cycle 24, a series of interplanetary coronal mass ejections (ICMEs) in the period 7–17 March 2012 caused geomagnetic storms that strongly affected high-latitude ionosphere in the Northern and Southern Hemisphere. GPS phase scintillation was observed at northern and southern high latitudes by arrays of GPS ionospheric scintillation and TEC monitors (GISTMs) and geodetic-quality GPS receivers sampling at 1 Hz. Mapped as a function of magnetic latitude and magnetic local time (MLT), the scintillation was observed in the ionospheric cusp, the tongue of ionization fragmented into patches, sun-aligned arcs in the polar cap, and nightside auroral oval and subauroral latitudes. Complementing a companion paper (Prikryl et al., 2015a) that focuses on the high latitude ionospheric response to variable solar wind in the North American sector, interhemispheric comparison reveals commonalities as well as differences and asymmetries between the northern and southern high latitudes, as a consequence of the coupling between the solar wind and magnetosphere. The interhemispheric asymmetries are caused by the dawn–dusk component of the interplanetary magnetic field controlling the MLT of the cusp entry of the storm enhanced density plasma into the polar cap and the orientation relative to the noon–midnight meridian of the tongue of ionization.